Public and private property claims in the Ottoman Empire : the beytülmal and its institutionalization in the early modern period - Çimen, Ayşegül (My University, 2023)
Bu tez, Osmanlı devleti bağlamında takriben/ yaklaşık 1450-1675 arasında mahlul (sahipsiz ve vârissiz) mal ve eşyaya dair yapılan hak talepleri konusunu inceler. Beytülmal kavramının farklı kullanım ve çağrışımları üzerinde yoğunlaşarak, kavramın daha dar bir özelliğini, mahlul mal/ eşya üzerinde hak sahibi olan hazine kalemi anlamını izah eder. İslam hukukunda kamunun mülkiyet iddialarının temel argümanlarını Osmanlı öncesi ve Osmanlı dönemi fıkıh eserleri üzerinden araştırdıktan sonra, Beytülmal’i merkeze alarak, mülkiyet iddiaları konusunda Osmanlı’da yöntemsel bir özgünlüğün olduğuna işaret eder. Teorik olarak, bu özgün anlamında beytülmal, belli mülkiyet iddialarında bireylerin haklarını korumak ve ihtiyaç sahibi kimselere maddi destek sağlamak için/ adına kurulmuştur. Zamanla çok yönlü bir yapı kazanarak kurumsallaşan beytülmal kalemi, Osmanlı’da fıkıh kitapları, kanunlar ve fetvalar aracılığıyla düzenlenmiştir. Beytülmalciler devlet tarafından yetkilendirilmiş görevlilerdir. Sahipsiz mal statüsünde olan kayıp ve kendisinden haber alınamayan kimselerin mallarını, terkedilmiş mal ve eşyaları ve varisi bulunmayan terekeleri teftiş eder, toplar ve kurum gözetiminde tutar. Beytülmalcinin peşine düştüğü bu mallar/ eşyalar bir bakla tanesi de olabilir, çok iyi bakılmış bir konak da. Beytülmal uygulamaları ve kurumu, Osmanlı imparatorluğunda hukuki ve mali bazı fonksiyonların belirli bir noktaya kadar yerine getirilmesini mümkün kılmıştır.

This dissertation focuses on public and private claims related to heirless and unclaimed property in the Ottoman context circa 1450-1675. It scrutinizes different connotations and uses of the concept of beytülmal to shed light upon a secondary and narrower meaning of the concept as a treasury office authorized to manage claims and revenue related to escheats and abandoned, lost, or other unclaimed property. The dissertation surveys the grounds of public property claims based on the works of legal scholars in the pre-Ottoman and Ottoman periods. It examines the formation of distinctive Ottoman methods that aim at assessing, settling, and managing claims regarding heirless and unclaimed properties or goods in the name of beytülmal. Beytülmal thus emerges as a revenue item and an office that sets responsibilities and procedures in time. Theoretically, the responsibility was to protect individual property rights and collect revenue to help needy subjects and provide other public services. Jurisprudential works (fıkıh), legal opinions (fetvas), and imperial regulations (kânûn) provide the basis of the beytülmal's complex organization. Beytülmalcis (as escheators of sorts) were authorized government officials who pursued, safeguarded, and converted to revenue the unclaimed properties of absent and missing individuals (gâib and mefkûd), and deserted (metrûk) and heirless properties. These properties might range from a piece of fava bean to a well-adorned mansion. Beytülmal practices enabled the Ottoman government to meet specific legal responsibilities regarding individual claims and acquire financial benefits to address particular public expenditures.
Osmanlı İmparatorluğu'nda kamu ve özel mülkiyet hakları : beytülmal ve erken modern dönemde kurumsallaşması
Keywords: Beytülmalci; Devlet mülkiyeti; Government ownership; Heirless; History; Inheritance; Muhallefat; Mülkiyet hakkı; Osmanlı İmparatorluğu, 1299-1918; Ottoman Empire, 1299-1918; Özel mülkiyet; Özelleştirme; Personal property; Privatization; Right of property; Sahipsiz mal; Tarih; Turkey; Türkiye; Unclaimed property; Varissiz Beytülmalci